Regional differences in prevalence, awareness, treatment and control of hypertension in Poland - comparison of two national multi-center health surveys: WOBASZ and WOBASZ II - Małgorzata Wierzowiecka; Justyna Marcinkowska; Andrzej Pająk; Magdalena Kozela; Jerzy Piwoński; Wojciech Drygas; Magdalena Kwaśniewska; Tomasz Zdrojewski; Krystyna Kozakiewicz; Andrzej Tykarski; Arkadiusz Niklas (PLoS ONE, 2025)
Introduction Data on regional differences in the current prevalence of hypertension in Poland remain limited. Objectives This study aimed to assess the prevalence, awareness, treatment, and control of hypertension among Polish adults in 2013–2014 (WOBASZ II study) and to compare these parameters with data from 2003–2005 (WOBASZ study). Patients and Methods The study was conducted in two independent, representative samples. The WOBASZ II study included 3,406 women and 2,757 men, while the WOBASZ study examined 7,783 women and 6,972 men. Results The greatest increase in hypertension prevalence over 10 years was observed among men from Świętokrzyskie Voivodeship (39.7% vs. 51.8%) and women from Łódzkie Voivodeship (32.7% vs. 44%). Increases in hypertension awareness were noted in men from Wielkopolskie Voivodeship (50.8% vs. 59.5%) and women from Świętokrzyskie Voivodeship (65.7% vs. 77%). Treatment rates rose in men from Warmińsko-Mazurskie Voivodeship (16.8% vs. 40.3%) and women from Opolskie Voivodeship (24.7% vs. 44.4%). Improvements in hypertension control were seen in men from Wielkopolskie Voivodeship (3.5% vs. 13.3%) and women from Lubuskie Voivodeship (5.6% vs. 27.4%). Conclusions Pronounced differences were observed in the prevalence, awareness, treatment, and control of arterial hypertension among voivodeships, highlighting the necessity of region-specific public health interventions and resource allocation to effectively manage hypertension. Additionally, changes observed over the decade from 2003/04–2013/14 highlight evolving epidemiological trends and demonstrate the impact of such interventions on hypertension management.